1982
DOI: 10.1148/radiology.144.3.6285413
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic classification of hepatic arterial collaterals.

Abstract: Hepatic artery collaterals in 40 patients who had had hepatic artery occlusion following peripheral or central embolization, surgical ligation, intra-arterial chemotherapy, or intimal injury from catheterization were studied. The collaterals were classified as intrahepatic or extrahepatic collaterals. Intrahepatic arterial collaterals develop in the portal triads and subcapsular area between the lobes of the liver. Extrahepatic arterial collaterals develop in the ligaments that suspend the liver in the periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(86 citation statements)
references
References 0 publications
2
83
0
1
Order By: Relevance
“…Michels has described the details of extrahepatic arterial collaterals to the liver after ligation of the hepatic artery in a series of 200 cases of hepatic resection, in which at least 26 possible routes of collateral arterial blood supply to the liver from the common hepatic trunk were noted [19] . Among them, the following are clinically important: (1) the subphrenic branch of the phrenic artery or internal mammary artery, (2) the aberrant hepatic artery, (3) the periductal arterial plexus, (4) other collaterals into the hepatic hilum from the superior mesenteric artery, and (5) the intrahepatic branches [19,20] . Although the significance of extrahepatic collateral pathways in association with liver damage after hepatic TAE has been reported [2,[21][22][23] , the relationship between the primary surgical procedure and the development of extrahepatic collaterals following hepatobiliary pancreatic surgery has not been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Michels has described the details of extrahepatic arterial collaterals to the liver after ligation of the hepatic artery in a series of 200 cases of hepatic resection, in which at least 26 possible routes of collateral arterial blood supply to the liver from the common hepatic trunk were noted [19] . Among them, the following are clinically important: (1) the subphrenic branch of the phrenic artery or internal mammary artery, (2) the aberrant hepatic artery, (3) the periductal arterial plexus, (4) other collaterals into the hepatic hilum from the superior mesenteric artery, and (5) the intrahepatic branches [19,20] . Although the significance of extrahepatic collateral pathways in association with liver damage after hepatic TAE has been reported [2,[21][22][23] , the relationship between the primary surgical procedure and the development of extrahepatic collaterals following hepatobiliary pancreatic surgery has not been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because some studies have shown that major bile ducts are also supplied by collaterals between the left and right hepatic arteries, the loss of a small arterial branch might not play an important role in the vitality of the biliary tree. [17][18][19] Analyzing early postoperative events, we found a significant increase in HAT in patients with complex arterial reconstruction (10.5% versus 2.0%). Some published reports support this result, 20,21 whereas other state opposite findings.…”
Section: Discussionmentioning
confidence: 99%
“…The development of collateral blood flow with one of the hepatic arteries being occluded was shown to be a possibility and to depend heavily on the site of vascular obstruction [26,27] . Hepatic interlobar arterial collaterals were exhaustively analyzed in autopsied specimens and corrosion casts [26][27][28][29][30] , as well as with radiological studies [31][32][33][34][35][36][37] called into being by the evolution of hepatic surgery, transplantation, interventional radiology, endovascular chemotherapy and embolization. Angiography demonstrated the interlobar branch-relayed collateral blood flow between the hepatic arteries [31][32][33][34][35][36][37] to be readily noted at the occlusion of either of the hepatic arteries [32,33,37] , which was demonstrated by computerized tomographic angiography in our Case 2 ( Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of investigators are in agreement that the interlobar collateral is extraparenchymal, passes cranial to the bifurcation of the PVs in the hepatic hilum in close proximity to the bile ducts [32,33,[37][38][39][40] and makes the crucial contribution of the blood supply to the biliary tract, as well as one of the hepatic lobes in the event of liver major route interruption [29,36,37,41] . So far it has not been clear whether there are transparenchymal branches to connect the hepatic lobes [31,33,36,42] . Case 2 demonstrates that LHA excision at a distal pancreatectomy with resection of CA and its branches is permissible by virtue of the fact that an arterial blood supply keeps coming to the left hepatic lobe thanks to the availability of the interlobar collateral.…”
Section: Discussionmentioning
confidence: 99%